Stand damage due to mono-cable winch and bulldozer yarding in a selectively logged tropical forest - YOSEP RUSLIM; RUSPITA SIHOMBING; YASON LIAH (Society for Indonesian Biodiversity, 2016)
Ruslim Y, Sihombing R, Liah Y. 2016. Stand damage due to mono-cable winch and bulldozer yarding in a selectively logged tropical forest. Biodiversitas 17: 222-228. Timber yarding with bulldozers has substantial unwanted environmental impacts and degrades the quality residual stands. We contrasted the impacts of bulldozer yarding with yarding with a sled-mounted mono-cablewinches equipped with 20 and 26 horsepower engines and 100 m of wire in a natural forest timber concession in East Kalimantan, Indonesia. We compared the two systems on the basis of productivity and stand damage in forests that were selectively logged at the same intensity on slopes ≤ 40% for bulldozer and for mono-cable yarding on slopes ≤55%. On slopes ≤40%, bulldozers yarded anaverage of 10.3 m 3 hm -1 hour -1 to roadside log landings whereas monoable winch productivity was 7.8 m 3 In these areas, mono-cable winching caused 1.2%, 2.0%, 0.6%, and 27.0% less damage to seedlings, saplings, poles, and trees than bulldozer yarding. Our study demonstrates that conventional methods such as bulldozer skidding created damage at seedling, sapling, pole and tree levels of vegetation around 15.3%, 9.9%, 10.8% and 34.5% at slope ≤40%. Winch-yarding is rare in tropical forestry, but the low cost of the mono-cable system we tested 3 day-1 for yarding distances that averaged 70.5 m, employment opportunities, and reduced environmental impacts indicate that such systems could make a major contribution to reduced-impact logging and promote local development.